Distribution of Aedes albopictus (Skuse 1895) in Tabasco México from 2015 to 2018 - Rodríguez-Martínez, Luis Miguel; Izquierdo-Aquino, Fernando; González-Fernández, Mariana Irina; Correa-Morales, Fabian; González-Acosta, Cassandra (Horizonte Sanitario, 2019)
Objective: To identify the distribution of Aedes albopictus (Skuse 1895) in Tabasco Mexico from 2015 to 2018. Material and Method: A cross-sectional observational descriptive study with a quantitative component was carried out. During January 2015 to July 2018, a total of 4,090 samples of Aedes sp. mosquito larvae were sent to the state public health laboratory for taxonomic identification from the 17 municipalities of Tabasco with 38 priority localities, which were collected from the state monitoring system of entomological surveillance with ovitraps. Results: Of the samples collected, 3,882 (94.91%) corresponded to Aedes aegypti and 208 (5.08%) to Aedes albopictus. The distribution of Aedes albopictus was identified in 9 municipalities representing 52.94% of affected municipalities with the presence of the vector and corresponds to 44.74% of localities sampled positive in the state of Tabasco. Conclusions: In this study it was determined the presence and distribution of Aedes albopictus, its dispersion in the state is in progress since it could colonize the 17 municipalities of the state. Due to the climate and vegetation characteristics, which poses new challenges in public health in terms of the prevention and control of arboviruses.  Keywords: Aedes albopictus; introduced species; Arbovirus; Disease vectors.